Dear founder : letters of advice for anyone who leads, manages, or wants to start a business - Webb, Maynard, 1955-; Adler, Carlye (St. Martin's Press, 2018)
More than 600,000 new businesses are launched each year. How can a start-up find the funding it needs to survive? When, if at all, should a company go public? How does an entrepreneur build and manage a workplace and create a lasting legacy? Maynard Webb has helped found, fund, and grow dozens of successful companies, and has driven strategic change at Salesforce, eBay, Everwise, and Visa, among other worldwide corporations. Known for offering savvy insight, encouragement, and a dose of reality in the form of engaging personal letters to a select group of business leaders, Webb now shares his lessons with the rest of America's aspiring entrepreneurs at any age and stage in their careers in Dear Founder. Featuring more than eighty inspiring, informative, and instructive letters, Dear Founder is rich with sound advice on an array of business topics, from turning your idea into a reality to building a culture, to reaching key financial goals. This book is an indispensable guide to navigating the realities, risks, and rewards of being your own boss and founding the company of your dreams.